Surface modified inorganic solid electrolyte material as well as preparation method and application thereof
By introducing a nano-oxide coating with a high dielectric constant on the surface of the inorganic solid electrolyte material, the problems of poor stability of sulfide and chloride solid electrolyte in the air and poor interfacial stability are solved, and solid electrolyte materials with high ionic conductivity and electrochemical stability are achieved.
Patent Information
- Application Number
- CN202411666047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-21
AI Technical Summary
The problem of poor stability of sulfide and chloride solid electrolytes in air and poor interface stability with the positive electrode material and the negative electrode material.
By introducing nano-oxides with dielectric properties as the cladding layer, the surface of the inorganic solid electrolyte material is discontinuously coated to form a surface modification layer. This nano-oxide material has a high dielectric constant, can effectively adjust the surface electric field, reduce the diffusion energy barrier of lithium ions, and improve the conduction ability of lithium ions.
High ionic conductivity, good air stability and electrochemical stability are achieved, which significantly improves the cycle stability of solid-state batteries and the reliability of commercial applications.
Smart Images

Figure CN119674196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a surface-modified inorganic solid-state electrolyte material and a preparation method and application thereof. Background Art
[0002] All-solid-state batteries have the advantages of high energy density and high safety, and therefore have become an important development direction of lithium-ion battery technology. As the most critical component of all-solid-state batteries, solid electrolytes determine their comprehensive performance. Inorganic solid electrolytes have attracted extensive attention and research from industry and academia. In the anion framework of sulfide and chloride solid electrolytes, S 2- and Cl - Compared to O 2- and F - With a larger ionic radius and smaller electronegativity, lithium ions are less attractive and can diffuse more easily in the lattice. Therefore, these materials have high ionic conductivity and strong deformability, and can be in close contact with active materials through cold pressing to achieve low interface resistance, which is conducive to solving the solid-solid interface contact problem in all-solid batteries. Based on the above characteristics, they have great potential in commercial applications.
[0003] According to the combination of precursors, sulfide solid electrolytes can generally be divided into three categories: (1) pseudo-binary sulfides, including Li2S+P2S5 pseudo-binary system (such as Li3PS4, Li7P3S 11 (2) Pseudo-ternary sulfides, including pseudo-ternary Li2S+P2S5+MS2 (M=Si, Ge or Sn, such as Li 10 GeP2S 12 , Li 10 SnP2S 12 ), and pseudo-ternary Li2S+P2S5+LiX (X=Cl, Br or I, such as lithium argyrodite electrolyte-Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 ); (3) Pseudo-quaternary sulfides, including Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 The general formula is Li 8.46 S 0.26 PS 0.22 Cl 0.07 Br 0.01 etc. They can all achieve more than 1 mS cm -1Despite its high ionic conductivity, it is easily corroded by moisture in the environment during storage and preparation, and reacts with water to produce harmful gas H2S, which destroys its structure and reduces ionic conductivity. Therefore, it faces the problem of poor air stability. In addition, under high voltage, sulfur atoms are easily oxidized to S 2- , which will lead to the destruction of the electrolyte structure. At the same time, it is also easy to occur S when matching with commercial layered positive electrode materials 2- Oxidation and exchange reactions increase the amount of byproducts generated at the solid electrolyte / positive electrode interface and make the all-solid-state battery less stable at high voltages. In addition, sulfide solid electrolytes are also easily reduced to form interfacial phases such as Li3P and Li2S when in contact with lithium metal negative electrodes, and continuous ion reduction reactions and failure phenomena cause short circuit problems in all-solid-state batteries. Therefore, it faces the challenges of high voltage positive electrode matching and matching with lithium metal negative electrodes.
[0004] According to the different crystal structures, chloride solid electrolytes can be divided into four types: (1) containing group IIIB metal elements or group 13 metal elements, with hexagonal close-packed crystal structure or cubic close-packed structure, such as trigonal or monoclinic system, such as Li3YCl6, Li2ZrCl6 and Li3InCl6; (2) containing divalent metal elements, with different forms such as olivine structure, spinel structure, twisted structure and Suzuki structure, such as Li2MgCl4; (3) containing lanthanide metal elements and presenting UCl3 type structure, such as Li 0.388 Ta 0.238 La 0.475 Cl3; (4) Amorphous structures containing oxygen and tending to be amorphous, such as xLi2O-MCl y , LiNbO4Cl and Li 1.75 ZrO 0.5 Cl 4.75 These electrolytes can achieve more than 1 mS cm -1 ionic conductivity. Similar to sulfides, chloride electrolytes are also susceptible to moisture corrosion in the environment during storage and preparation, leading to material hydrolysis. In addition, severe interfacial reactions occur when matching high-voltage layered cathode materials above 4.2 V, and electrolyte reduction reactions and short circuits are more likely to occur during matching with metallic lithium. Therefore, chloride electrolytes face challenges in matching high-voltage cathodes and lithium metal anodes.
[0005] In order to solve the problems of poor stability of sulfide solid electrolytes and chloride solid electrolytes in air and poor interface stability with positive and negative electrode materials, common modification methods for solid electrolytes include matrix structure doping and surface coating treatment. In terms of structural doping, anions with strong electronegativity (such as O 2-and F - ions) and cations with relatively soft acid characteristics (such as Sn 4+ , Sb 5+ Etc.). For example, Chinese invention patent application CN 117878387 A discloses a method for improving argyrodite-type sulfide electrolyte materials by co-doping two elements, O and C. The solid electrolyte material not only maintains the original high ionic conductivity, good mechanical strength and excellent negative electrode stability, but also has good air stability and positive electrode stability. Chinese invention patent application CN 118645682 A uses iodine-rich argyrodite-type electrolyte as a nucleating agent and dopant, and synthesizes a phosphorus-based argyrodite-type solid electrolyte modified by synergistic doping of multiple elements. In addition, Chinese invention patent application CN 118693336 A prepares an amorphous, doped halide solid electrolyte based on LiTaCl6 by co-doping with Zr, F and O, which maintains good ionic conductivity while also having good air stability and positive electrode stability. In terms of surface coating treatment, polymer semiconductors g-C3N4, ZnO, Al2O3, Li2CO3, Lewis acid treatment, trithiocyanate treatment and other methods are mainly used for coating. For example, Chinese invention patent CN 118712467 A significantly improves the air stability and enhances the electrochemical characteristics of solid-state batteries by coating a carbon-nitrogen-oxygen complex with a thickness of 0.05 μm to 0.4 μm onto a sulfide solid electrolyte with a particle size of 1 μm to 3 μm.
[0006] Although the above-mentioned literature and patents have achieved certain improvements in the air stability of inorganic solid electrolytes such as sulfides and chlorides and the electrochemical performance of solid-state batteries, they have not simultaneously solved the problems of decreased ionic conductivity of sulfide and chloride solid electrolytes due to doping and coating, poor air stability, and poor matching stability between the positive and negative electrodes, and the improvement measures are relatively complicated.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] In order to solve the above problems in the prior art, the present invention provides a surface-modified inorganic solid electrolyte material and a preparation method and application thereof, so as to realize a surface-modified inorganic solid electrolyte material with higher ionic conductivity, higher air stability and electrochemical stability.
[0009] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a surface-modified inorganic solid electrolyte material, comprising: Inorganic solid electrolyte materials, and A surface modification layer is non-continuously coated on the surface of the inorganic solid electrolyte material; wherein the surface modification layer is a nano-oxide with dielectric properties.
[0010] In the surface-modified solid electrolyte material provided by the present invention, by introducing a nano-oxide with dielectric properties as a coating layer, the surface electric field can be effectively adjusted, thereby reducing the lithium ion diffusion barrier and improving the lithium ion conductivity. Compared with sulfide or chloride solid electrolytes treated by other modification methods, the material has higher ion conductivity. At the same time, the introduction of the inert coating layer blocks the corrosion of the solid electrolyte by moisture in the environment and improves the humidity stability and storage performance. The present invention can obtain a solid electrolyte material that is excellent and reliable in commercial applications by stabilizing the matrix structure of the sulfide or chloride solid electrolyte and enhancing the electrochemical stability of the solid-state battery.
[0011] Preferably, the dielectric constant of the nano-oxide having dielectric properties is greater than 100.
[0012] More preferably, the dielectric constant of the nano-oxide having dielectric properties is greater than 200, such as 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, etc.
[0013] Preferably, the nano-oxide with dielectric properties includes BaTiO3, SrTiO3, CaTiO3, MgTiO3, MgTiO3, La(Mg 0.5 Ti 0.5 )O3 and La(Ni 0.5 Ta 0.5 )O3 one or more.
[0014] More preferably, the nano-oxide having dielectric properties comprises BaTiO3.
[0015] Preferably, the inorganic solid electrolyte material includes a sulfide solid electrolyte and / or a chloride solid electrolyte.
[0016] More preferably, the inorganic solid electrolyte material includes Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li7P2S8I 0.65 Br 0.35 、Li3InCl6、Li 1.6 ZrO 0.8 Cl4, LiNbOCl4 and Li 2.5 Y 0.5 Zr 0.5 One or more of Cl6.
[0017] Further preferably, the inorganic solid electrolyte material includes Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li7P2S8I 0.65 Br 0.35 and Li 2.5 Y 0.5 Zr 0.5 One or more of Cl6.
[0018] Preferably, based on the mass of the inorganic solid electrolyte material, the content of the nano oxide with dielectric properties is 1wt%~20wt%, for example, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%.
[0019] More preferably, based on the mass of the inorganic solid electrolyte material, the content of the nano-oxide with dielectric properties is 8wt% to 12wt%; further preferably, it is 10wt%.
[0020] Preferably, based on the primary particle size of the inorganic solid electrolyte material, the primary particle size of the nano-oxide with dielectric properties accounts for less than or equal to 5%, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4% or 5%.
[0021] More preferably, based on the primary particle size of the inorganic solid electrolyte material, the primary particle size of the nano-oxide with dielectric properties accounts for 0.5% to 1.5%; further preferably, it is 1%.
[0022] Preferably, the thickness of the surface modification layer is 20 to 200 nm, for example, it can be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm.
[0023] More preferably, the thickness of the surface modification layer is 50-150 nm; further preferably, it is 100 nm.
[0024] In the present invention, the introduction of the inert coating layer blocks the corrosion of the solid electrolyte by moisture in the environment and improves the humidity stability, air stability and storage performance. The storage conditions are that the relative humidity of the environment is 0.01%RH~100%RH; preferably, the relative humidity of the environment is 20%RH. The ambient temperature is -10~60℃; preferably, the ambient temperature is 25℃.
[0025] In a second aspect, the present invention provides a method for preparing the surface modified inorganic solid electrolyte material, comprising: mixing the inorganic solid electrolyte material and the nano-oxide having dielectric properties, and the obtained mixed material is the surface modified inorganic solid electrolyte material.
[0026] In the present invention, the preparation method of the surface modified inorganic solid electrolyte material includes any one of the following: (1) Mixing an inorganic solid electrolyte precursor material and a nano-oxide having dielectric properties to obtain a mixture. The inorganic solid electrolyte precursor material includes one or more of Li2S, P2S5 and LiCl.
[0027] (2) Mixing an inorganic solid electrolyte precursor material and a nano-oxide with dielectric properties to obtain a mixture, and then pressing the mixture into tablets and performing heat treatment. The tablet pressing pressure is 100-800 MPa; preferably, the tablet pressing pressure is 500 MPa. The diameter of the tablet is 5-50 mm, and the thickness of the tablet is 1-10 mm; preferably, the diameter of the tablet is 10 mm, and the thickness is 2 mm. The heat treatment temperature is 100-600 °C, and the heating and heat preservation time is 2-50 h; preferably, the heat treatment temperature is 400 °C, and the heating and heat preservation time is 5 h. The heating rate is 1-5 °C / min; preferably, the heating rate is 2 °C / min. The cooling rate is 1-10 °C / min; preferably, the cooling rate is 5 °C / min.
[0028] (3) Mixing an inorganic solid electrolyte material and a nano-oxide having dielectric properties to obtain a mixture.
[0029] (4) An inorganic solid electrolyte material and a nano-oxide having dielectric properties are mixed to obtain a mixture, and the mixture is then pressed into tablets and subjected to heat treatment.
[0030] Preferably, the inorganic solid electrolyte material and the nano-oxide having dielectric properties are mixed to obtain a mixture.
[0031] In the present invention, the mixing method may include manual mixing, ball mill mixing, mechanical fusion mixing or planetary ball mill mixing; preferably, planetary ball mill mixing is performed.
[0032] Preferably, the manual mixing time is 5 to 60 min; the rotation speed of the ball mill mixing is 100 to 600 rpm; more preferably, the ball mill rotation speed is 550 rpm.
[0033] Preferably, the linear speed of mechanical fusion is 5-40 m / s, and the fusion time is 2-10 min; more preferably, the linear speed of mechanical fusion is 10 m / s, and the fusion time is 5 min.
[0034] Preferably, the speed of the planetary high-speed ball mill is 200-800 rpm, and the mixing time is 2 min-10 h; more preferably, the speed of the planetary high-speed ball mill is 550 rpm, and the mixing time is 15 min. More preferably, the ball-to-material ratio of the planetary high-speed ball mill is 20-50:1; the further preferred ball-to-material ratio is 30:1.
[0035] The present invention found that appropriately extending the ball milling time is beneficial to the dispersion and coating effect of the nano-oxide, while too long a ball milling time will cause the solid electrolyte particle size to be significantly reduced and the grain boundaries to increase, which is not conducive to the conduction of lithium ions in the solid electrolyte. Therefore, choosing the appropriate ball milling time is crucial to achieving the best coating effect.
[0036] In the present invention, when the inorganic solid electrolyte material and the nano-oxide with dielectric properties are mixed, dry mixing or wet mixing can be adopted; preferably, dry mixing is adopted.
[0037] The method for preparing the surface-modified solid electrolyte material provided by the present invention adopts a short-time dry mixing technology. Compared with the existing coating technology, this method is more efficient, safe and environmentally friendly.
[0038] In a third aspect, the present invention provides the use of the surface modified inorganic solid electrolyte material in the preparation of an all-solid-state lithium battery.
[0039] In a fourth aspect, the present invention provides an all-solid-state lithium battery comprising the surface-modified inorganic solid electrolyte material.
[0040] In the present invention, the all-solid-state lithium battery is an all-solid-state lithium secondary battery. The all-solid-state lithium battery containing the above-mentioned surface-modified solid electrolyte material has lower battery impedance and higher electrochemical stability.
[0041] The surface-modified inorganic solid electrolyte material provided by the present invention, as well as its preparation method and application, adopts a solid electrolyte material with high ionic conductivity as a matrix, and introduces a nano-oxide coating layer with dielectric properties on the surface, thereby reducing the lithium ion diffusion barrier and improving the conductivity of lithium ions in the electrolyte. In addition, the coating layer with strong moisture stability and electrochemical stability also reduces the damage of moisture in the environment to the electrolyte and the reaction between the positive electrode material and the lithium metal negative electrode material and the electrolyte, thereby enhancing the stability of the solid-state battery under high pressure and inhibiting the formation of lithium dendrites, significantly improving the cycle stability.
[0042] At the same time, the method provided by the present invention is applicable to various inorganic solid electrolytes with excellent high ion conductivity, has simple operation steps, easy to obtain raw materials, low cost, and easy to promote industrialization. At the same time, the production efficiency is high and suitable for large-scale industrial production, the commercial application prospects are broad, and it has important theoretical and practical significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 This is a SEM image of the surface-modified inorganic solid electrolyte material of Example 1 provided by the present invention.
[0045] Figure 2 This is the XRD diagram of the surface-modified inorganic solid electrolyte material of Example 1 provided by the present invention.
[0046] Figure 3 This is a cycle performance diagram of the surface-modified inorganic solid electrolyte material of Example 1 and Comparative Example 1 provided by the present invention.
[0047] Figure 4 This is a SEM image of the surface-modified inorganic solid electrolyte material of Example 4 provided by the present invention.
[0048] Figure 5 This is the XRD diagram of the surface-modified inorganic solid electrolyte material of Example 4 provided by the present invention.
[0049] Figure 6 This is a SEM image of the surface-modified inorganic solid electrolyte material of Comparative Example 1 provided by the present invention.
[0050] Figure 7 This is the XRD diagram of the surface-modified inorganic solid electrolyte material of Comparative Example 1 provided by the present invention.
[0051] Figure 8 This is a SEM image of the surface-modified inorganic solid electrolyte material of Comparative Example 4 provided by the present invention.
[0052] Fig. 9 This is the XRD diagram of the surface-modified inorganic solid electrolyte material of Comparative Example 4 provided by the present invention. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0055] Example 1 This embodiment provides a solid electrolyte material of BaTiO3 coated with Li6PS5Cl, wherein the dielectric constant of BaTiO3 is 250; the specific steps of the preparation method are as follows: Weigh 0.15 g of BaTiO3 with a particle size of 50 nm and 1.5 g of Li6PS5Cl electrolyte with a median particle size of 10 microns, put them in a 50 mL ball mill, and put in Φ5 mm ZrO2 balls, with a ball-to-material ratio of 30:1 (wt%). Ball milling is carried out on a planetary high-energy ball mill, using dry ball milling without using any solvent. During ball milling, the raw materials are pre-milled at a low speed of 120 rpm, and the total time for low-speed pre-milling is 2 minutes, the purpose of which is to fully mix the raw materials. Then, high-speed ball milling is carried out at 550 rpm, and the total time for ball milling is 5 minutes. After the ball milling is completed, open the ball mill, pour out the ball milling beads, and perform a powder scraping operation to destroy the electrolyte powder that is caked on the inner lining of the ball mill. Finally, the electrolyte is crushed into powder with an agate mortar and bottled for use.
[0056] Figure 1 This is a SEM image of the Li6PS5Cl solid electrolyte (Li6PS5Cl@10BaTiO3) coated with BaTiO3 on the surface prepared in Example 1. The image shows that a large number of oxide particles close to 50 nm are coated on the sulfide particles, indicating that BaTiO3 is successfully coated on the sulfide solid electrolyte.
[0057] Figure 2The XRD structure diagram of the solid electrolyte shows the main characteristic peaks of the argyrodite-type Li6PS5Cl electrolyte, which indicates that the prepared sulfide solid electrolyte has a cubic structure crystal corresponding to the F-43m space group, and the space group number is 216. At the same time, the characteristic peaks of cubic BaTiO3 were found, indicating that BaTiO3 exists in the sulfide solid electrolyte and has no effect on the main structure of the sulfide electrolyte.
[0058] The following tests were performed on the sulfide solid electrolyte prepared in this example.
[0059] (1) The ionic conductivity test is as follows: 100 mg of electrolyte powder is weighed and placed in a special solid-state battery mold. It is pressurized at a pressure of 300 MPa and an AC impedance spectrum test is performed. The ionic conductivity of the sulfide solid electrolyte is calculated based on the impedance value and the Arrhenius formula. The calculation results are shown in Table 1.
[0060] (2) The air stability test is as follows: 100 mg of electrolyte powder is weighed and placed in a special air stability test chamber. The relative humidity of the test chamber is controlled at 20% RH and the temperature is controlled at 25 °C. The electrolyte is stored for 12 hours, and then the electrolyte is taken out for AC impedance spectroscopy test. The ionic conductivity of the solid electrolyte after exposure to moisture is calculated based on the impedance value and the Arrhenius formula. The calculation results are shown in Table 1. It can be found that the ionic conductivity after coating is as high as 5.2 mS / cm, and the ionic conductivity retention rate after exposure to air is as high as 61.5%.
[0061] (3) Electrochemical performance stability test is as follows: 100 mg of the surface modified electrolyte powder obtained in Example 1 is placed in a solid-state battery mold and pressed under a pressure of 300 MPa. The solid-state electrolyte powder is mixed with 1% lithium niobate (LiNbO3)-coated LiNi in an agate mortar. 0.8 Co 0.1 Mn 0.1 O2 (NCM811@Nb) electrode powder is fully mixed in a mass ratio of 3:7 to form a composite positive electrode powder. Take about 8 mg of the composite positive electrode powder and spread it evenly on one side of the electrolyte, and place a carbon-coated aluminum foil as the positive electrode current collector to separate the positive electrode from the stainless steel column. A lithium metal foil is attached to the other side of the electrolyte layer, and a copper foil is placed on the outside as the negative electrode current collector to separate the negative electrode from the stainless steel column. A pressure of 50 MPa is applied to the entire mold to ensure that all parts fit tightly. Constant current charge and discharge tests were carried out on a Blue Electric CT2001A battery charge and discharge tester. In the voltage range of 2.8~4.8V, the charge and discharge rate is 1C. The charge and discharge cycle curve of the all-solid-state battery assembled with the surface-modified inorganic solid electrolyte material obtained in Example 1 is shown in Figure 3It can be found that after 1600 cycles of charge and discharge, the discharge capacity retention rate reached about 80.9%, and the discharge specific capacity was as high as 122.2 mAh g -1 , showing good electrochemical cycling stability.
[0062] Example 2 This embodiment provides a BaTiO3 coated Li 5.5 PS 4.5 Cl 1.5 The solid electrolyte material is prepared in the same manner as in Example 1, except that Li6PS5Cl is replaced by an equal amount of Li 5.5 PS 4.5 Cl 1.5 .
[0063] The ion conductance of Example 2 before and after exposure to a relative humidity of 20% RH for 12 hours is shown in Table 1. It can be seen that the ion conductance after coating is as high as 6.2 mS / cm, and the ion conductance retention rate after exposure to air is as high as 69.4%.
[0064] Example 3 This embodiment provides a BaTiO3 coated Li7P2S8I 0.65 Br 0.35 The solid electrolyte material is prepared in the same manner as in Example 1, except that Li6PS5Cl is replaced by an equal amount of Li7P2S8I 0.65 Br 0.35 .
[0065] The ion conductance of Example 3 before and after exposure to a relative humidity of 20% RH for 12 hours is shown in Table 1. It can be seen that the ion conductance after coating is as high as 2.6 mS / cm, and the ion conductance retention rate after exposure to air is as high as 73.1%.
[0066] Example 4 This embodiment provides a BaTiO3 coated Li 2.5 Y 0.5 Zr 0.5 Cl6 solid electrolyte material, the specific steps of its preparation method are as follows: Weigh 0.15 g of BaTiO3 with a particle size of 50 nm and 1.5 g of Li with a median particle size of 10 μm. 2.5 Y 0.5 Zr 0.5Cl6 electrolyte was placed in a 50 mL ball milling jar, and Φ5 mm ZrO2 balls were placed, with a ball-to-material ratio of 30:1 (wt%). Ball milling was carried out on a planetary high-energy ball mill, using a dry ball milling method without using any solvent. During ball milling, the raw materials were pre-milled at a low speed of 120 rpm for a total of 2 minutes, in order to fully mix the raw materials. Then, high-speed ball milling was performed at 550 rpm for a total of 5 minutes. After the ball milling was completed, the ball milling jar was opened to pour out the ball milling beads, and the powder was scraped and bottled for later use.
[0067] Figure 4 The surface-coated BaTiO3 Li 2.5 Y 0.5 Zr 0.5 Cl6 solid electrolyte (Li 2.5 Y 0.5 Zr 0.5 The SEM image of Cl6@10BaTiO3) shows that a large number of oxide particles with a diameter of nearly 50 nm are coated on the chloride particles, indicating that BaTiO3 is successfully coated on Li 2.5 Y 0.5 Zr 0.5 Cl6 chloride solid electrolyte.
[0068] Figure 5 The XRD structure diagram of the solid electrolyte shows the main characteristic peaks of the trigonal crystal structure with hexagonal close packing, which indicates that the prepared chloride solid electrolyte has a trigonal structure crystal corresponding to the P4mm space group, and the space group number is 99. At the same time, the characteristic peaks of cubic BaTiO3 were found, indicating that BaTiO3 exists in the chloride solid electrolyte and has no effect on the main structure of the chloride electrolyte.
[0069] The following tests were performed on the chloride solid electrolyte prepared in this example.
[0070] (1) The ionic conductivity test is as follows: 100 mg of electrolyte powder is weighed and placed in a special solid-state battery mold, which is pressed at a pressure of 300 MPa. The AC impedance spectrum test is performed, and the ionic conductivity of the chloride solid electrolyte is calculated based on the impedance value and the Arrhenius formula. The calculation results are shown in Table 1. It can be seen that coating BaTiO3 does not cause Li 2.5 Y 0.5 Zr 0.5 The decrease in the ionic conductivity of the Cl6 electrolyte.
[0071] (2) The air stability test is as follows: 100 mg of electrolyte powder is weighed and placed in a special air stability test chamber. The relative humidity of the test chamber is controlled at 20% RH and the temperature is controlled at 25 °C. The electrolyte is stored for 12 h, and then the electrolyte is taken out for AC impedance spectroscopy test. The ionic conductivity of the solid electrolyte after exposure to moisture is calculated based on the impedance value and the Arrhenius formula. The calculation results are shown in Table 1. It can be found that the ionic conductivity of the material after exposure is still as high as 1.03 mS cm -1 , the retention rate reached 87.3%, indicating that coating BaTiO3 can improve the air stability of chloride electrolyte.
[0072] Example 5 This embodiment provides a BaTiO3-coated Li3InCl6 solid electrolyte material, and its preparation method is the same as that of Example 1, except that Li6PS5Cl is replaced by an equal amount of Li3InCl6.
[0073] The ion conductance of Example 5 before and after exposure to a relative humidity of 20%RH for 12 hours is shown in Table 1. It can be seen that the ion conductance after coating is only 0.35 mS / cm, and the ion conductance retention rate after exposure to air is 82.9%. It can be seen that the effect is slightly worse than that of Examples 1 to 4.
[0074] Example 6 This embodiment provides a BaTiO3 coated Li 1.6 ZrO 0.8 Cl4 solid electrolyte material, the preparation method is the same as that of Example 1, except that Li6PS5Cl is replaced by an equal amount of Li 1.6 ZrO 0.8 Cl4.
[0075] The ion conductance of Example 6 before and after exposure to a relative humidity of 20% RH for 12 hours is shown in Table 1. It can be seen that the effect is slightly worse than that of Examples 1 to 4.
[0076] Example 7 This embodiment provides a BaTiO3 coated Li 1.6 ZrO 0.8 The preparation method of Cl4 solid electrolyte material is the same as that of Example 1, except that Li6PS5Cl is replaced by an equal amount of LiNbOCl4.
[0077] The ion conductivity of Example 7 before and after exposure to a relative humidity of 20% RH for 12 hours is shown in Table 1. It can be seen that although the ion conductivity is higher than that of Examples 1 to 4, the ion conductivity retention rate after exposure to air is slightly poor.
[0078] Example 8 This embodiment provides a BaTiO3-coated Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that the amount of BaTiO3 used is 0.18 g.
[0079] The ion conductivity of Example 8 before and after exposure to a relative humidity of 20% RH for 12 hours is shown in Table 1. It can be seen that although the ion conductivity is higher than that of Examples 1 to 4, the ion conductivity retention rate after exposure to air is slightly poor.
[0080] Example 9 This embodiment provides a BaTiO3-coated Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that the amount of BaTiO3 used is 0.13 g.
[0081] The ion conductivity of Example 9 before and after exposure to a relative humidity of 20% RH for 12 hours is shown in Table 1. It can be seen that although the ion conductivity is higher than that of Examples 1 to 4, the ion conductivity retention rate after exposure to air is slightly poor.
[0082] Comparative Example 1 This comparative example provides a Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that BaTiO3 is replaced by an equal amount of Li6PS5Cl.
[0083] Comparative Example 2 This comparative example provides a Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that BaTiO3 is replaced by an equal amount of Li 5.5 PS 4.5 Cl 1.5 .
[0084] Comparative Example 3 This comparative example provides a Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that: Li7P2S8I 0.65 Br 0.35 .
[0085] Comparative Example 4 This comparative example provides a Li 2.5 Y 0.5 Zr 0.5 Cl6 solid electrolyte material, the preparation method is the same as that of Example 1, the only difference is that BaTiO3 is replaced by an equal amount of Li 2.5 Y 0.5 Zr 0.5 Cl6.
[0086] Comparative Example 5 This comparative example 1 provides a Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that BaTiO3 is replaced by an equal amount of Li3InCl6.
[0087] Comparative Example 6 This comparative example 1 provides a Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that BaTiO3 is replaced by an equal amount of Li 1.6 ZrO 0.8 Cl4.
[0088] Comparative Example 7 This comparative example 1 provides a Li6PS5Cl solid electrolyte material, and its preparation method is the same as that of Example 1, except that BaTiO3 is replaced by an equal amount of LiNbOCl4.
[0089] The ion conductance of Comparative Examples 1 to 7 before and after exposure to a relative humidity of 20%RH for 12 hours is shown in Table 1. It can be seen that the ion conductance of Comparative Examples 1 to 6 before exposure is smaller than that of Example 1, indicating that the coating process causes the ion conductance to decrease, but coating BaTiO3 can improve its lithium ion conduction. At the same time, the ion conductance of Comparative Examples 1 to 7 after exposure to 20%RH for 12 hours all dropped significantly, indicating that the humidity stability of the uncoated electrolyte material is poor, further proving that the improvement effect of coating BaTiO3 is better.
[0090] The SEM morphology and XRD structure of Comparative Example 1 are shown in Figure 6 and Figure 7 , showing a cubic crystal structure of argyrodite type. The charge and discharge cycle curve of the all-solid-state battery assembled in Comparative Example 1 is shown in Figure 3 It can be found that after 600 cycles of charge and discharge, the discharge capacity retention rate has decayed to about 69.3%, and the discharge specific capacity is only 79 mAh g -1 , indicating that its electrochemical stability is poor. The SEM morphology and XRD structure of Comparative Example 2 are shown in Figure 8 and Fig. 9 , showing a hexagonal close-packed trigonal crystal structure.
[0091] Table 1 Ion conductivity test results of electrolyte materials
[0092] According to Table 1, when the inorganic solid electrolyte material in the surface modified inorganic solid electrolyte material is Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li7P2S8I 0.65 Br 0.35 , Li2.5 Y 0.5 Zr 0.5 The ionic conductivity and air stability of the electrolyte are better when Cl6 is used.
[0093] In summary, the present invention coats a nano-oxide with dielectric properties (such as BaTiO3) onto a sulfide or chloride material through a short mechanical ball milling process to obtain the surface-modified solid electrolyte described in the present invention. Since the nano-oxide with dielectric properties can reduce the transmission energy barrier of lithium ions in the electrolyte, the room temperature lithium ion conductivity of the modified solid electrolyte is significantly higher than that of the unmodified material. At the same time, the ion conductivity of the solid electrolyte material after exposure to 20% RH for 12 hours decreases slightly and is still higher than 1 mS cm -1 The modified solid electrolyte matches the commercial layered cathode material and lithium anode material and shows excellent cycle stability performance: compared with the ordinary unmodified solid electrolyte, the cycle life of the all-solid-state battery can be increased by more than 1000 weeks, which is a solid electrolyte with the potential for commercial application.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A surface-modified inorganic solid electrolyte material, characterized in that: include: Inorganic solid electrolyte materials, and A surface modification layer is non-continuously coated on the surface of the inorganic solid electrolyte material; wherein the surface modification layer is a nano-oxide with dielectric properties.
2. The surface-modified inorganic solid electrolyte material according to claim 1, characterized in that: The dielectric constant of the nano-oxide with dielectric properties is greater than 100.
3. The surface-modified inorganic solid electrolyte material according to claim 1 or 2, characterized in that: The nano-oxides with dielectric properties include BaTiO3, SrTiO3, CaTiO3, MgTiO3, MgTiO3, La(Mg 0.5 Ti 0.5 )O3 and La(Ni 0.5 Ta 0.5 )O3 one or more.
4. The surface-modified inorganic solid electrolyte material according to any one of claims 1 to 3, characterized in that: The inorganic solid electrolyte material includes a sulfide solid electrolyte and / or a chloride solid electrolyte; preferably, the inorganic solid electrolyte material includes Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 、Li7P2S8I 0.65 Br 0.35 、Li3InCl6、Li 1.6 ZrO 0.8 Cl4, LiNbOCl4 and Li 2.5 Y 0.5 Zr 0.5 One or more of Cl6.
5. The surface-modified inorganic solid electrolyte material according to any one of claims 1 to 4, characterized in that: Based on the mass of the inorganic solid electrolyte material, the content of the nano-oxide with dielectric properties is 1wt%~20wt%.
6. The surface-modified inorganic solid electrolyte material according to any one of claims 1 to 5, characterized in that: Taking the primary particle size of the inorganic solid electrolyte material as a benchmark, the primary particle size of the nano-oxide with dielectric properties accounts for less than or equal to 5%.
7. The surface-modified inorganic solid electrolyte material according to any one of claims 1 to 6, characterized in that: The thickness of the surface modification layer is 20-200 nm.
8. The method for preparing the surface-modified inorganic solid electrolyte material according to any one of claims 1 to 7, characterized in that: include: The inorganic solid electrolyte material and the nano-oxide with dielectric properties are mixed to obtain a mixed material which is the surface-modified inorganic solid electrolyte material.
9. Use of the surface-modified inorganic solid electrolyte material according to any one of claims 1 to 6 or the surface-modified solid electrolyte material prepared by the preparation method according to claim 8 in the preparation of an all-solid-state lithium battery.
10. An all-solid-state lithium battery, characterized in that: It contains the surface-modified inorganic solid electrolyte material according to any one of claims 1 to 6 or the surface-modified solid electrolyte material prepared by the preparation method according to claim 8.
Citation Information
Patent Citations
Solid electrolyte material, preparation method, electrolyte layer and lithium ion battery
CN117878387A
Modified sulfide solid electrolyte as well as synthesis method and application thereof
CN118645682A
Halide solid electrolyte and preparation method and application thereof
CN118693336A
Sulfide solid electrolyte material and preparation method and application thereof
CN118712467A
Secondary battery
CN103262316A
Cited By
Composite solid electrolyte and method for preparing the same
CN122511985A